Factors affecting internasionalisation of Malaysian manufacturing SMEs - Afsharghasemi, Akbar (2013)
The dissertation investigated factors contributing to the internationalisation of small and medium sized manufacturing enterprises in Malaysia. As a newly industrialized country, the Malaysian economy predominantly depends on the small and medium enterprise (SME) sector. However, this research seeks to redress this by reporting the key drivers influencing the internationalisation process of SMEs such as firm specific,key personnel and environmental factors as well as to determine the role of market turbulence and competitive advantage on internationalization of manufacturing SMEs in Malaysia. To empirically test the developed framework, primary data was gathered using the survey questionnaire method. The survey instrument was distributed to all manufacturing SMEs involved in exporting which are located in the Klang Valley of Malaysia (FMM, 2012) which are 770 firms. In order to examine the causal structure of the research framework, Structured Equation Modelling (SEM) technique was utilised in this research. A total of 257 questionnaires were usable and analysed. This study has obtained a better understanding on factors that influence internationalisation of manufacturing SMEs by provided an empirical evidence for effect of firm resource, entrepreneurial orientation and market orientation on internationalisation as firm specific factors. Furthermore, it has determined the effect of human capital as key personnel factor as well as government regulation as an environmental factor on internationalisation of manufacturing SMEs in Malaysia. Furthermore, the study has added to the body of knowledge by introducing competitive advantage as a mediating variable between firm resources, entrepreneurial orientation, market orientation,human capital and government regulation with internationalization of manufacturing SMEs in Malaysia. Last but not least, in this study market turbulence found to moderate the relationship between entrepreneurial orientation and internationalization of manufacturing SMEs in Malaysia in high market turbulence situation. Based on the influential variables obtained from the analysis, an integrated model was developed which predicted 68% of variance in internationalization of SMEs in Malaysia.